The Effect of Good Corporate Governance on Profitability Ratio (Studi Kasus Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020) - Lilis Kartika (Journal of Bussines Management Basic, 2023)
The core problem in this study is the ineffectiveness  of the implementation  of the company's  good corporate governance (GCG), especially in the company's profitability which has decreased from 2018 - 2020. This study aims to determine the effect of good corporate governance (GCG) disclosure on the company's profitability ratio. GCG in this case is proxied with the board of commissioners, board of directors and audit committee. Meanwhile, the profitability variable is proxied with ROA (Return On Assets). This study used a multiple linear regression method and for hypothesis testing, F test, t test and determination  test  were  used  with  a  total  sample  of  36.  The  population  of  this  study  is  banking companies on the Indonesia Stock Exchange in the 2018-2020 period and sampling techniques, namely purposive sampling methods. The results showed that the variables of the board of commissioners had a negative and significant effect on roa, the board of directors had a positive and significant effect on ROA, the audit committee had no effect and significantly affected ROA. Simultaneously, the board of commissioners, the board of directors and the audit committee have no and significant effect on the ROA.